Thermal and mechanical properties laboratory evaluation of hollow brick made of fired clay and rice husk additive (2020)
Hollow bricks in fired clay for masonry are important in design and construction of buildings. Their thermal and mechanical properties must be considered because of the impact they have on energy consumption. The objective of this research is to evaluate thermal and mechanical properties of a new hollow brick, called Eco Design, made of fired clay and rice husk additive, in order to identify the benefits of its use in the construction of masonry walls in regions with a tropical climate. The methodology develops simulation of thermal properties of brick, manufacturing at the laboratory level and characterization of mechanical properties of finished product. Thermal validation simulates the behavior of heat transfer and fluxes of Eco Design in mixtures of 100% fired clay, 95% -5%, 85% -15% and 70% -30% fired clay with rice husk, respectively. Eco Design samples are manufactured by extrusion and fired at 1000 °C. The characterization of mechanical properties of samples manufactured consists of determining dimensions, water absorptive capacity, linear shrinkage, mass losses and mechanical resistance to compression according to Colombian normative. The results indicate that Eco Design brick has a thermal benefit of 6.9 °C in 95% -5% mixture, as the percentage of rice husk increases, benefit increases 0.75 °C additional. Furthermore, the implementation of rice husk additive improves 7.15% mechanical resistance to compression and increases 18.3% water absorption capacity. Finally, the assessment of thermal and mechanical properties of Eco Design is a reference to promote innovation in ceramic industry in Norte de Santander and Colombia.